MANAGEMENT EVENT SENI PERTUNJUKAN PERFORMANCE ART - Syafrizal, Syafrizal; Efi, Agusti; Budiwirman, Budiwirman (Gorga : Jurnal Seni Rupa, 2022)
Performance art is an activity of staging the work of artists who use the body as a medium for their work. This study aims to explain the performance performance management of performance art performance art. The type of research used is qualitative research. The research stage is carried out by collecting literature sources, both primary and secondary. The results showed a performance art management process which includes research, design (design), division of tasks and responsibilities, determining the right sponsor, communication and coordination between teams and evaluation. Carrying out an event requires careful coordination and preparation so that the event can be managed more efficiently and effectively. Keywords: management, event, performance, performance art. Abstrak Performance art merupakan kegiatan pementasan hasil karya para perupa yang menggunakan tubuh sebagai media berkaryanya. Penelitian ini bertujuan untuk memaparkan manajemen pergelaran seni pertunjukan performance art. Jenis penelitian yang digunakan adalah penelitian kualitatif. Tahapan penelitian dilaksanakan dengan menghimpun sumber kepustakaan, baik primer maupun sekunder. Hasil penelitian menunjukkan proses manajemen performance art yang meliputi riset, desain (rancangan), pembagian tugas dan tanggung jawab, menentukan sponsor yang tepat, komunikasi dan koordinasi antar tim dan evaluasi . Melaksanakan suatu event memerlukan koordinasi serta persiapan yang matang agar event bisa dikelola dengan lebih efisien serta efektif. Kata Kunci: management, event, pertunjukan, performance art. Authors: Syafrizal : Universitas Negeri Padang Agusti Efi : Universitas Negeri Padang Budiwirman : Universitas Negeri Padang References: Ayuni, Astari & Efi, Agusti. (2020). Manajemen Festival Seni Pertunjukan Pekan Nan Tumpah Di Provinsi Sumatera Barat. Padang. Universitas Negeri Padang Sumatera Barat. Brantas. (2009). Dasar-Dasar Manajemen. Jakarta: Alfabeta. Hasibuan, M. S. (2001). Manajemen Sumber Daya Manusia. Jakarta: Bumi Aksara. Isnanta, S. D. (2010). Representasi Tubuh Perempuan Dalam Performance Art Karya Melati Suryadarmo. Brikolase: Jurnal Kajian Teori, Praktik dan Wacana Seni Budaya Rupa, 2(1). Kusuma, Rr. Chusnu Syarifa Diah. (2016). Modul Manajemen Event. Modul. Yogyakarta: Universitas Negeri Yogyakarta. Lubis, S. K., Retnowati, T. H., & Syawalina, S. (2020, July). Predictive Power of Intellectual Ability Test Score on Students™ Fine Art Learning Outcomes. In 3rd International Conference on Arts and Arts Education (ICAAE 2019) (pp. 41-44). Atlantis Press. Prayhogi, I. (2016). Penciptaan Video Musik dengan Materi Performance Art (Doctoral dissertation, State University of Surabaya). Rochbeind, F., & Pristiati, T. (2022). Analysis of Movement and Music Characteristics of Performance Art in œTouching the Heart for a Broken Wing Performance. Harmonia: Journal of Arts Research and Education, 22(1), 119-128. Safroni, K. H .M. Ladzi. (2012), Manajemen dan Reformasi Pelayanan Publik dalam Konteks Birokrasi Indonesia (Teori, Kebijakan, dan Implementasi). Yogyakarta: Aditya Media. Saputro, Johan. (2014). Perencanaan Event Management Festival Kesenian Yogyakarta sebagai Media Komunikasi Identitas Yogyakarta. Yogyakarta: Universitas Islam Negeri Sunan Kalijaga Yogyakarta. Sedyawati, Edi. (1981). Pertumbuhan Seni Pertunjukan. Jakarta: Sinar Harapan. Supriyadi, S. (2017). Community of Practitioners: Solusi Alternatif Berbagi Pengetahuan antar Pustakawan. Lentera Pustaka: Jurnal Kajian Ilmu Perpustakaan, Informasi Dan Kearsipan, 2(2), 83-93. Terry, George. R., & Rue, L. W. (2010). Dasar-dasar Manajemen. Jakarta: Bumi.